PENERAPAN PENDIDIKAN AKHLAK IBU RUMAH TANGGA DI DESA PERBATASAN ( STUDI FENOMENOLOGIS DI DESA PERBATASAM SUMATERA UTARA DAN SUMATERA BARAT ) - Syafnan, Syafnan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2019)
This study aims to reveal: morals education implementation of housewives in multi-ethnic villages, provincial border areas, both in the event of grief, joy, and activities of the village government. Implementation morality of the intended housewife is the prominent behavior that is shown to others in social activities.The research methodology is a qualitative phenomenological model, with key data sources are 15 housewives aged 20 to 47 years, the instruments used are guidelines for structured interviews and observations, and data processing that starts from collecting, validating, analyzing, triangulating, and making conclusion.Research results: 1. Housewives are always vigilant in the use of daily time to be in a place of disaster, dress neatly without opening aurat, and giving donations; 2. Participating in the village program, especially national ceremonies, and village training activities in the field of creative handicrafts; 4. Developing the morals of their children by relying on the Alquran Education Park